2022
DOI: 10.1177/20503121221094212
|View full text |Cite
|
Sign up to set email alerts
|

Hematological abnormalities among adults with type 1 diabetes mellitus at the University of Gondar Comprehensive Specialized Hospital

Abstract: Objective: Changes in the blood cell function, metabolism, and the coagulation system were associated with diabetes mellitus. This study aimed to determine the magnitude and associated factors of hematological abnormalities in adults with type 1 diabetes mellitus. Methods: A total of 204 medical charts of adults with type 1 diabetes mellitus who registered for follow-up at the University of Gondar Comprehensive Specialized Hospital were reviewed from June to August 2021. Data were collected using a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Complete blood count (CBC), fasting blood glucose levels (FBG), post prandial blood glucose levels (PPBG), glycated hemoglobin levels (HbA1C), ESR, liver functions tests, and renal functions tests were assessed for all subjects as described before. 11,12 Detection of IFNλ-4 rs73555604 and ERAP rs26618 polymorphisms…”
Section: Hematological and Biochemical Investigationsmentioning
confidence: 99%
“…Complete blood count (CBC), fasting blood glucose levels (FBG), post prandial blood glucose levels (PPBG), glycated hemoglobin levels (HbA1C), ESR, liver functions tests, and renal functions tests were assessed for all subjects as described before. 11,12 Detection of IFNλ-4 rs73555604 and ERAP rs26618 polymorphisms…”
Section: Hematological and Biochemical Investigationsmentioning
confidence: 99%
“…Acute complications include symptoms such as hypoglycemia, hyperglycemic crises, hyperglycemic hyperosmolar state and diabetes ketoacidosis. Chronic complications include diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, microvascular complications, and haematological abnormalities (Lim, 2014;Nentwich and Ulbig, 2015;Chawla et al, 2016;Okonofua et al, 2021;Getawa and Adane, 2022;Okonofua et al, 2023).…”
Section: Complications Of Diabetes Mellitusmentioning
confidence: 99%
“…In this regard, studies indicated that BMI, waist circumference (WC), and waist-to-hip ratio (WHR) anthropometric index are comparable in predicting diabetes onset and following complications [ 9 , 10 ]. Moreover, patients with diabetes usually illustrated abnormalities in their laboratory findings [ 11 , 12 ]. The WHR associated with fasting blood sugar (FBS) levels, proteomic profile, and lipid profiles reflect its role in assessing metabolic health.…”
Section: Introductionmentioning
confidence: 99%